Lansoprazole-Based Colorimetric Chemosensor for Efficient Binding and Sensing of Carbonate Ion: Spectroscopy and DFT Studies - Darroudi, Mahdieh; Mohammadi Ziarani, Ghodsi; Bahar, Shahriyar; Ghasemi, Jahan B.; Badiei, Alireza (Frontiers in Chemistry, 2021)
A benzimidazole based receptor can be used as a colorimetric sensor. The Lansoprazole chemosensor titration was performed with cations and anions; however, only the interactions with CO32- ion was significant in high selectivity and sensitivity. It was characterized by the displacement of the absorbance bands at 285 nm to 390 nm in ethanol. The anion recognition occurs through exhibiting color alteration from colorless to yellow and enhancing the absorption. Overall, the UV-Vis detection limit of chemosensor lansoprazole L for CO32- ion was calculated by the calorimetric method as 57 μM. The binding stoichiometry between chemosensor L and CO32- was found to be 1:1. Moreover, theoretical studies were performed to acquire an electronic description of the complexation mechanism by CO32- as well as to study bonding and structure in the complex. The optimized structures and binding mechanisms were supported with a high correlation and agreement by spectroscopy and DFT calculations.